Implementation of population administration services in Tuban district - Suryawati, Nany (Linguistics and Culture Review, 2021)
The purpose of this study is to provide public administration services, namely: (1). Meet every resident in public service (2). Increase the awareness of the population to fulfill the population (3). Implement development policies. Methods: This research uses a qualitative approach, data collection techniques are: interviews, site surveys, documentation and literature studies. Conclusion: (1). The administration of sub-district government in population administration services in Tuban Regency has been in accordance with Indonesian Law No. 23 of 2006 (2). Settlement of Population administration problems, involving related elements and can be resolved in accordance with population regulations.